THE OPTIMIZATION COUNSELING GUIDANCE BY BHABINKAMTIBMAS TO PREVENT CRIMINAL ACTIONS OF FRAUD IN POLRES PEKALONGAN CITY - RIFQI RAMADITYA (Advances in Police Science Research Journal, 2022)
This research is caused by the high number of reports of criminal cases of fraud at the Pekalongan City Police that are not balanced with the settlement cases. The crime of fraud can be prevented through counseling guidance efforts by Bhabinkamtibmas Pekalongan City Police. experienced fraud. This study aims to determine the implementation of counseling guidance by Bhabinkamtibmas Polres Pekalongan City and how to optimize counseling guidance by Bhabinkamtibmas. This research uses qualitative approach and field research methods, namely by collecting data in the field or observing, interviewing, and researching documents that discuss counseling guidance. The researcher applies management theory (George R. Terry), SWOT theory and management elements. . Bhabinkamtibmas of the Pekalongan City Police has carried out counseling guidance properly and according to procedures.But, the implementation is not optimalized yet because human resources were not understand about newest fraud tecnique and the target doesn’t appropiate with the objective or goal.